Estimation of heterosis in okra (Abelmoschus esculentus) for fruit yield and its components using line × tester mating design - SINGH, B; GOSWAMI, AAKANSHA; SHARMA, A K (The Indian Journal of Agricultural Sciences, 2016)
Okra [Abelmoschus esculentus (L.) Moench] cultivars were sown during the kharif season 2013-14 at Horticulture Research Centre, Department of Horticulture, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut (UP), India, developed and maintained for using conventional agronomic practices to keep the crop in good condition. Fifty one F1 hybrids developed from crossing between 20 okra parents using line × testers (17 Line × 3 Testers) mating design, evaluated during the kharif season 2013-14 at Horticulture Research Centre, Department of Horticulture, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut (UP), India. Genetic material was developed and maintained by following standard conventional agronomic practices to keep the crop in good condition. Out of 51 cross combinations, some crosses showed the significant heterosis over better parent and mid parent. Seven and twenty six crosses were founded significant for early flowering twenty six and thirty three crosses were showed significant positive heterosis for higher yield over better parent and mid parent, respectively. It is pertinent to mention that the crop has potential to produce the heterotic cross combinations and such crosses can be use for further improvement of this crop. Six crosses, namely, VRO1668×AK, IC11527×AK, VRO3×AK, VRO5×AK, FB10×PK and BO2×AK were found potential for fruit yield and other desired characters. This indicates that the cross can be exploited commercially for high yield potential.